ICHNOLOGICAL STUDY OF SHALLOW MARINE ENDOLITHIC SPONGES FROM THE ITALIAN COAST (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1989)
Living boring sponges belonging to eight species of the genera Siphonodictyon, Cliona and Cliothosa, were collected from the limestone seafloor of the Apulian coast. Samples were taken in zero to -20 m water depth. Spicule preparations from the sponges, and epoxy casts of the borings, facilitated a comparison of the animal and its work. The borings were analyzed ichnotaxonomically and attributed to 11ichnospecies of Entobia. Direct correlation between biospecies and ichnospecies was not found in all cases.Several ichnospecies are new, and some of these are named using Pleistocene material. The new ichnospecies are Entobia gigantea, E. magma and E. parva.
Keywords: Sponge borings; Entobia; Ichnotaxonomy; Recent; Fossil; Mediterranean Sea.